Implementasi Aturan Hukum Dalam Program Universal Health Coverage Terhadap Kesejahraan Anak Disabilitas Di Indonesia - Yaya Suryana; Sri Retno Widyorini (PSHPM Untag Semarang, 2025)
The Universal Health Coverage (UHC) program in Indonesia aims to provide welfare in the health sector to the community as a whole. The state, as a provider and guarantor of health welfare, assumes responsibility for the development and care of children throughout Indonesia, without exception, including children with disabilities. This study aims to understand more about the future welfare of children with disabilities and the implementation of existing legal regulations in Indonesia in responding to the program. The research method used in this study involves normative legal research, where the method seeks a legal basis, by analyzing legislation related to child welfare. The results of the study show that the government has made great efforts in implementing legal regulations for the welfare of children with disabilities. However, there are still several obstacles and shortcomings in practice, including lack of socialization, limited data, budget constraints faced by the government, limited accessibility for children with disabilities, and inadequate health related to human resources and facilities. The purpose of establishing legal regulations and implementing them is to realize equal rights and opportunities for the health of people with disabilities towards Universal Health Coverage